2017
DOI: 10.1016/j.worlddev.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Effects of Large-Scale Agricultural Investment: Conceptual Considerations and Estimated Employment Effects

Abstract: Summary. -Large-scale agricultural investments (LSAIs) in general and their socio-economic implications in particular have been heavily debated in recent years. While some claim that LSAIs are an important catalyst for development in neglected rural areas, others caution that they pose a risk to rural communities' livelihoods. The extent to which LSAIs provide benefits for local communities is hence still contested. This paper sets out to conceptually understand what effects the establishment of a large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 50 publications
2
41
0
1
Order By: Relevance
“…The early stage of vine propagation is reported to be less K-demanding than the storage root production stage in mature crops (Taraken et al 2010). Other studies have also shown that the effect of K on the growth of sweetpotato occurred at least Labor intensity (LI) defined as the amount of labor needed in production process and is calculated as the number of workers required to cultivate 1 ha of a specific crop" (Nolte and Ostermeier, 2017) pp. 432 It is used to anlayze statistical differences between two groups in a sample 7 weeks after planting (Bourke 1985;Byju and George 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The early stage of vine propagation is reported to be less K-demanding than the storage root production stage in mature crops (Taraken et al 2010). Other studies have also shown that the effect of K on the growth of sweetpotato occurred at least Labor intensity (LI) defined as the amount of labor needed in production process and is calculated as the number of workers required to cultivate 1 ha of a specific crop" (Nolte and Ostermeier, 2017) pp. 432 It is used to anlayze statistical differences between two groups in a sample 7 weeks after planting (Bourke 1985;Byju and George 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite much conjecture, there is very limited evidence on the ways in which the rise of these medium‐scale African farmers affects smallholder farmers. Most of the speculation has centered around smallholders’ restricted access to land and potential marginalisation resulting from large‐scale farm land acquisitions (Messerli et al ., ; Anseeuw et al ., ; Nolte and Ostermeier, ; Nolte and Sipangule, ). These are important concerns, to be sure.…”
Section: Introductionmentioning
confidence: 98%
“…The consequences of such slow transformations of the institutional environment of community development have also been sufficiently studied. They are currently manifested in employment problems, and thus the growth of welfare and money laundering in favour of more developed areas Mishchuk & Grishnova, 2015;Nolte & Ostermeier, 2017;Osabuohien et al, 2019) , the negative impact on natural resources due to the investor's narrow interest in their development (Bleyer et al, 2016;Kováč et al, 2020), while productive land use is already complicated within communities due to obstacles that may be driven by land ownership (Katona et al, 2017). However, despite the developed methodological tools of strategic planning of regional development, the availability of opportunities for its use in the form of international programs of logistical assistance and advisory support, investment in the development of local communities is still chaotic.…”
Section: Introductionmentioning
confidence: 99%